PENGARUH ANEMON (Heteractis magnifica) TERHADAP VITALITAS IKAN BADUT (Amphiprion oscellaris) UNTUK MEMINIMALISASI PENGGUNAAN KARANG HIDUP PADA AKUARIUM LAUT BUATAN - Muhammad Zainuddin Lubis; Sri Pujiyati; Muhammad Mujahid (Fakultas Perikanan dan Ilmu Kelautan, 2013)
Sea Anemone is a close relative of corals. It is one of the marine life that is favored by lovers of sea-water ornamental Aquarium. Its body form resembling sponges with a beautiful color on her body. This sea anemone is a software belongs to the animals of animal invertebrates (spineless animals back). However, in the cultivation of fish, Clown fish which is much used living coral. The use of excess numbers of Anemone coral reef ecosystems in a dwindling and threatened to extinction. The results of this research show that the vitality of the living surroundings Amphiprion oscellaris aquariums made by an ideal aquatic environment conditions is not affected by symbiosis with Heteractis magnefica. Amphiprion oscellaris fish maintenance doesn't need sea anemone to survive, so the use of sea anemone can be minimised and replacing with artificial Anemone akuaskap as a decoration.